Economic survey 2007 - 08 - India. Ministry of Finance (New Delhi, 2008)
Economic Survey is a flagship annual document of the Ministry of Finance, Government of India, which is laid in the two houses of the Parliament one day before the presentation of the Union Budget. It summarizes the government policy initiatives as well as performance on major development programmes covering all the sectors of the economy. The focus of the report is largely on developments in the preceding fiscal / financial year. The Survey comes with a detailed Statistical Appendix covering information on all aspects of the economy-macro as well as sectoral. The document brings together information and analysis on economic development which is of use to policy analysts, researchers, students, media and the civil society.
Keywords: Economic survey - 2007 - 08